SOIL OF PAMETIKARATA, EAST SUMBA: ITS SUITABILITY AND CONSTRAINTS FOR FOOD CROP DEVELOPMENT - B. H. Prasetyo; Hendri Sosiawan; Sofyan Ritung (Indonesian Agency for Agricultural Research and Development, 2000)
Pametikarata, Lewa subdistrict, is the priority area for food crop development in East Sumba. To evaluate its suitability and constraints, chemical properties, suitability and fertility capability classification for rice and secondary crops of some potential soils have been studied both in the field and in the laboratory. Seven soil profiles consisted of forty one soil samples were subjected to chemical and mineralogical analyses in the laboratory. The analyses consisted of clay fraction and organic-carbon contents, pH, potential P and K (25% HCI extraction), available P, phosphate retention. Exchangeable cations and cation exchange capacity (NH4OAc 1N, pH 7), and mineralogical composition of the clay fraction. The results indicate that soil acidity varies from acid to neutral Exchangeable cations are dominated by Ca cation and soil CEC ranges from low to very high. Clay mineral composition also varies, some are dominated by montmorillonite, others show mixed mineralogy between montmorillonite and kaolinite, and the rests are dominated by kaolinite with the exception of wet Vertisols, all soils are grouped as marginally suitable (S3) for rice and secondary crops. Nutrient availability and retention are the common limiting factors. Using fertility capability classification (FCC), all soils are grouped as clayey soils with low infiltration and high water holding capacity. The serious constraint for food crop development in this area is uncontrolled grazing that makes a conflict of interests between farming and cattle herding systems. Optimum success of food crop development in the area could be reached by controlling the herding system and improving the existing agricultural system.